The Ethos of Volunteers of Non-Formal Education Collectives Originated from Civil Society [el Ethos de Voluntarios de Colectivos de Educación No Formal Originados Desde la Sociedad Civil] - Pasmanik-Volochinsky, D; Rodriguez-Araneda, M (Pontificia Universidad Catolica de Valparaiso, 2019)
We report the results of the reconstruction of the ethos of volunteers who work in Chile in community educational projects generated from civil society. They are mainly university students from Social Sciences careers. We presume that the participation in an educative and political project, that demands a sustained devotion in time, would be characterized by a particular ethics sense, aligned with its ends and mediated in volunteering practices. Information was sought employing semi-structured interviews, analyzed qualitatively by means of the constant comparison method. The field work was done on 2014, after the country had experienced an inflection in its political history with the presidential elections that lead to the end of twenty years of governments of the coalition Concertación de Partidos por la Democracia. On 2019 some of the same volunteers were interviewed again. The results show an ethos with nuclear elements and other that differentiate between two groups, one of temporally volunteers and another of volunteers that integrate volunteering in its life project. Political contingency doesn t seem to influence ethos conformation. © 2019 Pontificia Universidad Catolica de Valparaiso. All rights reserved.